2013
DOI: 10.1097/coh.0b013e328363d3b7
|View full text |Cite
|
Sign up to set email alerts
|

Nonreplicating vectors in HIV vaccines

Abstract: Purpose of review We review the broad spectrum of nonreplicating viral vectors which have been studied extensively, from preclinical studies through clinical efficacy trials, and include some of our most promising HIV vaccine candidates. Recent findings The success of the RV144 trial, with an ALVAC (canarypox)-based regimen, contrasts with the failures of the Adenovirus 5-based regimens in the Step study, the Phambili study (HVTN 503), and the HVTN 505 study which was recently modified to halt vaccinations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…98 In addition, efficacy using Ad5-based vectors was limited in phase IIb clinical trials. 96 Early human clinical studies using a canarypox-based vector (ALVAC) demonstrated modest HIV antibodies and low cellular responses. 99,100 However, a prime-boost regimen with ALVAC and a recombinant gp120 boost showed significant protection against acquiring HIV infection in the RV144 vaccine trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…98 In addition, efficacy using Ad5-based vectors was limited in phase IIb clinical trials. 96 Early human clinical studies using a canarypox-based vector (ALVAC) demonstrated modest HIV antibodies and low cellular responses. 99,100 However, a prime-boost regimen with ALVAC and a recombinant gp120 boost showed significant protection against acquiring HIV infection in the RV144 vaccine trial.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other viral vector systems have been tested for their ability to induce HIV-specific B cell responses. [95][96][97] Replicationdeficient poxvirus-and adenovirus-based vaccines are perhaps the best studied viral vectors in the context of an HIV vaccine. Early immunogenicity studies of nonreplicating adenovirus expressing HIV-1 env in mice showed that a boost was required to induce anti-HIV-1 Env antibodies using higher titers of vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…These live-vector-based vaccines use genetically attenuated pathogens to express viral antigens and stimulate the host immune system. Although live-vector-based vaccines can induce robust T-cell and B-cell immune responses, manufacturing of live organism-based vaccines as well as inherent antivector immunity observed in the general population are major obstacles to overcome [16][17][18]. A prime example of the latter is Merck and Co.'s (NJ, USA) STEP study, Phase II clinical trial that was stopped in 2007 [19].…”
Section: Live Vaccine Vectors For Vaccination Against Hiv-1mentioning
confidence: 99%
“…Poxviruses have been studied extensively as gene transfer vectors (10). A large packaging capacity for recombinant DNA, precise virusspecific control of target gene expression, a lack of persistence of genomic integration in the host, and high immunogenicity when used as a vaccine make poxviruses very attractive as gene delivery systems for the development of new vaccines (11).…”
mentioning
confidence: 99%